An Assessment of Project-Based Learning Implementation in Christian Religious Education: A Case Study at IAKN Ambon - Benjamin Metekohy; Abetsina Lumalessil; Frilyan Joksan Korsely; Febrian Saija (Sekolah Tinggi Teologi Kadesi Yogyakarta, 2026)
This study aims to assess the effectiveness of Project-Based Learning (PjBL) in enhancing learning outcomes in Christian Religious Education (CRE) at IAKN Ambon. Specifically, it evaluates how PjBL influences students’ theological writing, scriptural interpretation, and reflective learning competencies. Employing a pre-experimental one-group pre-test–post-test design, the research involved 30 sixth-semester CRE students selected through purposive sampling. Data were collected through standardized assessments administered before and after the implementation of PjBL-focused instructional projects. The results show a significant improvement in students’ academic performance, particularly in their ability to construct theological arguments, interpret biblical texts, and engage in reflective theological analysis. The findings conclude that PjBL provides a meaningful learning framework that fosters collaborative inquiry, independent research, and integrative thinking. This study contributes to Christian Religious Education scholarship by offering empirical evidence on the pedagogical value of PjBL and highlighting its potential as an instructional model to strengthen higher-order theological competencies in Indonesian theological institutions.